ANALISIS PELAKSANAAN ADMINISTRASI PENDIDIKAN DI KB PERMATA BUNDA DESA MANDI ANGIN KECAMATAN INDRALAYA SELATAN KABUPATEN OGAN ILIR - Vlora Veronika; Hashifa Aulia Putri; Dea Ananda; Bella Effendi; Silvi Amanda; Hilwa Inaz Tazkiyah (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
ABSTRACT Educational administration is an essential component in supporting the effective implementation of Early Childhood Education (ECE), as it plays a vital role in managing students, educators, instructional planning, and institutional documentation in a systematic manner. This study aimed to describe the implementation of educational administration at KB Permata Bunda, focusing on student admission administration, the management of teacher and student data, daily learning schedules, and instructional administration through the Daily Learning Implementation Plan (RPPH) and Weekly Learning Implementation Plan (RPPM). The study employed a qualitative approach using a descriptive method. Data were collected through direct observation and documentation of administrative records available at KB Permata Bunda. Data were analyzed using qualitative descriptive techniques, including data reduction, data display, and conclusion drawing. The findings revealed that the institution had implemented educational administration in a structured manner, as reflected in the availability of institutional administrative records, teacher and student data, daily learning schedules, RPPH, and RPPM that served as guidelines for instructional activities. However, the student admission process was still conducted manually, limiting the efficiency of administrative data management. The study concludes that the existing administrative system has effectively supported the implementation of learning activities, while strengthening digital-based administration is recommended as a strategic direction to improve the efficiency and quality of educational services in the future. ABSTRAK Administrasi pendidikan merupakan komponen penting dalam mendukung efektivitas penyelenggaraan Pendidikan Anak Usia Dini (PAUD) karena berperan dalam mengelola peserta didik, tenaga pendidik, perencanaan pembelajaran, serta berbagai dokumen kelembagaan secara sistematis. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan administrasi pendidikan di KB Permata Bunda yang mencakup administrasi penerimaan peserta didik, pengelolaan data pendidik dan peserta didik, jadwal kegiatan pembelajaran, serta administrasi pembelajaran melalui Rencana Pelaksanaan Pembelajaran Harian (RPPH) dan Rencana Pelaksanaan Pembelajaran Mingguan (RPPM). Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan melalui observasi langsung dan dokumentasi terhadap berbagai dokumen administrasi yang tersedia di KB Permata Bunda pada tanggal 24 Februari 2026. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan secara deskriptif. Hasil penelitian menunjukkan bahwa administrasi pendidikan di KB Permata Bunda telah dilaksanakan secara terstruktur melalui tersedianya administrasi kelembagaan, data pendidik dan peserta didik, jadwal kegiatan harian, RPPH, serta RPPM yang menjadi pedoman pelaksanaan pembelajaran. Meskipun demikian, administrasi penerimaan peserta didik masih dilaksanakan secara manual sehingga belum sepenuhnya mendukung efisiensi pengelolaan data. Penelitian ini menyimpulkan bahwa sistem administrasi yang diterapkan telah mendukung penyelenggaraan pembelajaran secara efektif, namun penguatan pemanfaatan teknologi berbasis digital menjadi prospek pengembangan untuk meningkatkan kualitas layanan administrasi pendidikan di masa mendatang.